BASIS ETIKA LINGKUNGAN HIDUP MASYARAKAT TRADISIONAL MADURA - Hasani Utsman (UIN Raden Mas Said Surakarta, 2018)
This study aims to describe the environmental ethical values of Maduranese traditional society. Their belief to nature, especially related to the land and sea landscape is manifestation form of shifting paradigm: from anthropocentrism to the spirit of biocentrism-ecocentrism, become the basis for the environmental ethics development. Based on the ethnographical approach, the moral view of Maduranese traditional society is obtained through participant observation and direct interaction, the results of this study revealed that Maduranese traditional society put forward two main principles in interacting to the nature, i.e. harmony and belief to the supernatural forces, which is led to the diversity of the land use typology and nature’s rituals. For land use context, the cosmology of Maduranese traditional society is more complicated and rigorous, because the ecological factors of Madura are dominated by uneven mooring compared to the ecology of Java Island which is dominated by rice fields. The Maduranese's traditional society belief system to nature seems more syncretic than the tradition of the people in Java Island.